PKM Pelatihan Kepemimpinan dan Manajemen Bagi Pengurus Organisasi Santri di Ponpes Al-Amien Bugih Pamekasan - Muhammad Darrin Zuhri; Moh Kamaluddin; Mohammad Rudiyanto; Syaiful Anam (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This article discusses the implementation and results of leadership and management training for the officials of a Santri organization in Ponpes Al-Amien Bugih Pamekasan, Indonesia. The program was conducted to improve the leadership and management skills of Santri organization officials in order to enhance their organizational performance and prepare them for future careers. The training method used in this program was a combination of lectures, discussions, case studies, and simulations, with the aim of providing participants with practical knowledge and skills.The results of the program showed significant improvements in the leadership and management skills of Santri organization officials, including their ability to communicate effectively, manage resources efficiently, and make strategic decisions. Moreover, the program also had a positive impact on the organization's performance, such as increasing the number of members, improving the quality of organizational activities, and enhancing the organization's reputation in the community.The success of the program can be used as an example for other educational institutions to adopt similar programs to enhance the leadership and management skills of their students or santri. However, there are also challenges that need to be addressed, such as limited resources and lack of support from authorities. Collaborative efforts and continuous innovation are needed to overcome these challenges and improve the quality of the training program. In conclusion, the leadership and management training for Santri organization officials in Ponpes Al-Amien Bugih Pamekasan provides significant benefits for participants, organizations, the workforce, and the community as a whole. The program's success and continued improvement can contribute to the advancement of education and leadership and management skills in Indonesia.